2023
DOI: 10.3389/fpsyg.2022.1039025
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual review of the effectiveness of flipped learning in vocational learners’ cognitive skills and emotional states

Abstract: An inverted method of teaching is an instructional model where traditional classroom activities take place before class while class time is devoted to discussion, problem-solving, and interaction among students. Flipped learning is a learner-centered and technology-driven approach that benefits from the inverted method of teaching. Recently, instructors have begun to employ innovative pedagogies like flipped learning approach, to change the conventional practices in vocational education as flipped learning giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Specifically, students found that the use of video lectures gave them enough time to acquire sentence structure, and they believed that the online materials and videos used in their English class were effective in helping them learn. The findings of this study are consistent with Zhou's (2023) suggestion that flipped learning, as a form of blended learning, can provide benefits not just to learners but also to instructors and parents. As a result, it should be considered a valuable approach for vocational education.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, students found that the use of video lectures gave them enough time to acquire sentence structure, and they believed that the online materials and videos used in their English class were effective in helping them learn. The findings of this study are consistent with Zhou's (2023) suggestion that flipped learning, as a form of blended learning, can provide benefits not just to learners but also to instructors and parents. As a result, it should be considered a valuable approach for vocational education.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, to understand the impact of flipped learning on vocational learners, Zhou (2023) analyzed previous studies on the effect of flipped learning on cognitive skills and emotional states. The results of these investigations indicated that flipped learning had a significant positive impact on learners' engagement, motivation, self-efficacy, critical thinking, problem-solving, learning skills, learning strategies, and communicative competence.…”
Section: Related Studies Of the Flipped Instructional Modelmentioning
confidence: 99%
“…Another limitation of this study was that the default settings of the test software used are limited to group observations and do not allow individual tracking. It is likely that an FC depends on student performance, meaning that higher-level learners students outperform compared to lower-level learners [69]. In future studies, we will observe students as individuals.…”
Section: Improved Feedback To Learnersmentioning
confidence: 95%
“…Similarly, Baskara (2023) stated that chat robots can help increase motivation and ensure participation. The flipped learning approach is a teaching strategy that can be used in vocational education, according to Zhou (2023). Fonseca et al (2023) stated that increased student engagement and data to evaluate their performance were the most frequently cited benefits; they identified the increase in time and effort spent by teachers and students as the most encountered difficulties.…”
Section: Literature Reviewmentioning
confidence: 99%